Exogenous application of hydrogen sulfide donor attenuates inflammatory reactions through the L‐selectin‐involved pathway in the cutaneous reverse passive Arthus reaction. Issue 4 (1st April 2013) - Shimizu, Kazuhiro; Ogawa, Fumihide; Hara, Toshihide; Yoshizaki, Ayumi; Muroi, Eiji; Yanaba, Koichi; Akiyama, Yuichiro; Yamaoka, Toshifumi; Sato, Shinichi
Abstract : H2S donor attenuates inflammatory responses through the L‐selectin involved pathway, in the cutaneous reverse passive Arthus reaction. Abstract : H2 S has been highlighted recently as an endogenous, gaseous signaling molecule, especially in inflammations. The deposition of IC induces an acute inflammatory response with tissue injury. To assess the roles of H2 S in the IC‐induced diseases, the cutaneous, reverse passive Arthus reaction was conducted using NaHS as a H2 S donor. Furthermore, we conducted similar experiments using selectin −/− mice to determine the involvement of selectin molecules in the H2 S‐mediated pathway. Exogenous application of NaHS dramatically attenuated inflammatory reactions in WT mice associated with Arthus reaction. Namely, mRNA expressions of TNF‐α, IFN‐γ, and neutrophil numbers were reduced significantly in the lesional skins of NaHS‐treated WT mice relative to untreated ones. NaHS treatment significantly reduced these three parameters in the lesional skins of E‐ and P‐selectin −/− mice but not in those of L‐selectin −/− mice. Quite similar results were obtained in the blocking study using WT mice injected with mAb to E‐, P‐, and L‐selectin. Our results indicated that the exogenous application of NaHS attenuates inflammatory responses in reverse passive Arthus reaction through a L‐selectin‐involved pathway but not through E‐ or P‐selectin pathways.